Health service utilization in Manicaland Province, Zimbabwe during the COVID-19 pandemic: results from a cross-sectional household survey - Julia Scott; Melissa S Nolan; Joseph Mberikunashe; Oscar Tapera; Mufaro Kanyangarara (Journal of Global Health Reports)
# Background